Motor inhibition from the brainstem is normal in torsion dystonia during REM sleep. Issue 2 (February 1991) - Fish, D R; Sawyers, D; Smith, S J; Allen, P J; Murray, N M; Marsden, C D
Abstract : The maintenance of axial atonia during REM sleep was monitored in 14 patients with primary torsion dystonia, 10 patients with secondary torsion dystonia, and 10 normal subjects using submental EMG and video EEG telemetry. The excitability of the corticospinal tract during REM sleep was also assessed using scalp magnetic stimulation in seven patients and three controls. During REM sleep dystonic patients had well maintained atonia evidenced by infrequent bursts of submental activity, no episodes of complex semi-purposeful behaviour and reduced motor responses to magnetic stimulation. These findings suggest that the inhibitory centres in the region of the locus coeruleus and their descending pathways to the spinal alpha motor neurons are intact in torsion dystonia.